Block copolymers of N‐vinyl carbazole and α,ω‐dihydroxy polydimethylsiloxane - Akar, Ahmet; Kizilcan, Nilgun; Ustamehmetoglu, Belkis; Colak, Demet; Sarac, A. Sezai; Colak, Cengiz (Wiley, 2007)
AbstractThe redox system of ceric ammonium nitrate (Ce4+) and α,ω‐dihydroxy polydimethylsiloxane (DH.PDMS) was used to polymerize N‐vinyl carbazole (NVCz) to produce poly(N‐vinylcarbazole)‐b‐α,ω‐dihydroxy polydimethylsiloxane(PNVCz‐b‐DH.PDMS). The ratio of NVCz/ceric salt/DH.PDMS has an important effect on the properties of formed copolymers. White insulating PNVCz‐b‐PDMS copolymers with high fluorescence intensity are produced if the ratio of ceric salt/ NVCz is below 0.2. Green conductive PNVCz‐b‐PDMS copolymers are produced if this ratio is well above 0.2. The concentration and the type of DH.PDMS affected the polymerization yield. PNVCz‐b‐DH.PDMS copolymers were also prepared by electroinduced polymerization in the presence of catalytic amount of Ce4+ in a divided electrochemical cell where Ce3+ is readily oxidized to Ce4+ at the anode. White insulating PNVCz‐b‐DH.PDMS copolymers show higher contact angle value and lower Tg values than of white poly(N‐vinyl carbazole) (PNVCz). © 2007 Wiley Periodicals, Inc. J Appl Polym Sci, 2007